STRATEGI KOMUNIKASI PEMASARAN DESTINASI WISATA PANTAI SIGANDU DI KABUPATEN BATANG - Mj Rizqon Hasani; Nikolaus Ageng Prathama (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2022)
This study was conducted to determine the marketing communication strategy for the object of Sigandu Beach and the things that support and hinder the marketing implementation of the Batang Regency Culture and Tourism Office. This study uses the phenomenological method. The informants consisted of visitors to the research site, tourism actors, tourism organizations and the head of the Marketing and Tourism Business Promotion Division of the Culture and Tourism Office. The data used in this study is a combination of primary data and secondary data. Data collection techniques with interviews and documentation. Data analysis, data reduction, data presentation and conclusion drawing. The result of the research is that the Regional Government of Batang Regency through the Department of Culture and Tourism has implemented a marketing communication strategy designed internally without involving tourism actors in planning. Marketing of Sigandu Beach tourism is carried out by integrated marketing communications (IMC) through advertising, public relations, sales promotion and personal selling. Marketing communication strategies, among others, focus on; image, natural attraction, community support and technological progress. Marketing communication strategies that highlight the uniqueness of Sigandu, namely clean natural panoramas and the attractiveness of tourist facilities such as outbound, animal attractions, etc.